Plasma electrolytic oxidizing liquid, anticorrosive aluminum foil pretreatment method and aluminum-plastic film

The aluminum foil is surface modified by plasma electrolytic oxidation technology to form an oxide film layer through plasma electrolytic oxidation technology, which solves the problem of corrosion of aluminum foil in lithium batteries, and further improves the electrolyte resistance performance by introducing zinc ions, achieving an environmentally friendly and efficient flexible packaging solution for lithium batteries.

CN115354377BActive Publication Date: 2025-04-04浙江华正能源材料有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211131130.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-16
Publication Date
2025-04-04
Estimated Expiration
2042-09-16

AI Technical Summary

Technical Problem

In existing lithium battery flexible packaging, aluminum foil is easily corroded by the corrosive components of the electrolyte, resulting in battery failure, and the commonly used chromate passivation treatment poses a risk of environmental pollution.

Method used

Plasma electrolytic oxidation technology is used, and phosphate solution is used as the electrolyte, and aluminum foil is used as the anode for microarc oxidation to form an oxide film layer, thereby improving the corrosion resistance of the aluminum foil, and enhancing the crystallinity of the oxide film layer by introducing zinc ions.

Benefits of technology

It effectively improves the electrolyte resistance and adhesive properties of aluminum foil, avoids the risk of environmental pollution of chromate, and optimizes the overall performance of the flexible packaging of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115354377B_ABST
    Figure CN115354377B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of lithium battery soft packaging, and more specifically, it relates to a plasma electrolytic oxidation solution, an anticorrosive aluminum foil pretreatment method and an aluminum-plastic film. A plasma electrolytic oxidation solution is a phosphate-containing electrolyte solution, which includes raw materials of the following concentrations: 0.1-0.2 mol / L zinc acetate, 0.01-0.03 mol / L disodium ethylenediaminetetraacetate and 0.015-0.08 mol / L sodium hexamethaphosphate. The plasma electrolytic oxidation solution of the present application replaces chromate for aluminum foil passivation by plasma electrolytic oxidation, and the prepared aluminum foil has excellent bonding properties and electrolyte resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium battery soft packaging, and more specifically, to a plasma electrolytic oxidation solution, an anti-corrosion aluminum foil pretreatment method and an aluminum-plastic film. Background Art

[0002] Lithium-ion batteries have developed rapidly since their introduction due to their advantages such as high specific energy, long cycle life and low self-discharge rate, and the market size has expanded rapidly. Aluminum-plastic film, as the packaging material of soft-pack lithium batteries, is mainly composed of an outer protective layer, an intermediate aluminum foil layer and an inner heat-sealing layer, and plays a certain role in protecting the internal core material.

[0003] However, since the main component of the electrolyte inside the battery is LiPF6, LiPF6 is corrosive to a certain extent, and when it comes into contact with water it will generate extremely corrosive hydrofluoric acid, which can corrode the middle layer of aluminum foil, thereby causing the battery to fail.

[0004] At present, the conventional method is to passivate the aluminum foil with chromate to improve its corrosion resistance. However, if the chromate is not properly disposed of after use, the chromate is likely to cause harm to the environment and affect aquatic life. Summary of the invention

[0005] In order to improve the problem that chromate is likely to cause harm to the environment and affect aquatic life, the present application provides a plasma electrolytic oxidation solution, an anti-corrosion aluminum foil pretreatment method and an aluminum-plastic film.

[0006] In a first aspect, the present application provides a plasma electrolytic oxidizing solution, which adopts the following technical solution:

[0007] A plasma electrolytic oxidizing liquid is a phosphate-containing electrolyte solution.

[0008] Micro-arc oxidation (MAO) technology is currently a common surface modification technology, also known as plasma electrolytic oxidation. It uses aluminum foil as the anode and immerses it in an electrolyte. In a strong electric field formed by high voltage and high current, the aluminum foil is pulled from the Faraday zone of anodization to the high-voltage discharge zone, forming a micro-arc discharge on its surface. Under the oxidation reaction, an oxide film layer of a certain thickness grows on the surface of the aluminum foil.

[0009] Compared with other surface modification technologies, plasma electrolytic oxidation has the advantages of simple process, environmental protection, low cost and high production efficiency. In addition, the electrolyte used in plasma electrolytic oxidation also abandons chromate, thus directly eliminating the possibility of improper disposal of chromate causing harm to the environment and affecting aquatic life.

[0010] In addition, the electrolyte currently used in plasma electrolytic oxidation is usually a sodium silicate solution. However, the applicant has found that, compared with the sodium silicate solution, when the electrolyte is a phosphate solution, the aluminum foil after plasma electrolytic oxidation has better adhesion and electrolyte resistance.

[0011] The reason may be that during the electrolysis process, the conductivity of phosphate is better than that of silicate, which leads to the fact that phosphate can effectively accelerate the formation of oxide film, thereby obtaining a greater oxide film thickness in the same time, effectively improving the electrolysis resistance of aluminum foil. In addition, phosphate also has excellent hydrophilicity, which promotes the excellent bonding performance of aluminum foil after plasma electrolytic oxidation.

[0012] Preferably, the plasma electrolytic oxidizing solution contains phosphate ions and zinc ions.

[0013] By adopting the above technical solution, zinc ions are further introduced into the plasma electrolytic oxidation solution, thereby effectively enhancing the crystallinity of the oxide film layer and further improving the electrolyte resistance of the aluminum foil after plasma electrolytic oxidation.

[0014] Moreover, zinc ions can also form a zinc phosphate coating with phosphate ions on the surface of the aluminum foil. Since zinc phosphate has excellent activity, the zinc phosphate coating can also form a complex complex with the aluminum ions in the aluminum foil, thereby promoting the aluminum foil after plasma electrolytic oxidation to have better electrolyte resistance.

[0015] Preferably, the plasma electrolytic oxidation solution contains zinc acetate, disodium ethylenediaminetetraacetate and sodium hexametaphosphate.

[0016] The ratio of zinc ions to phosphate ions in a simple zinc phosphate solution remains constant, but as the proportion of phosphate ions increases, the aluminum foil after plasma electrolytic oxidation has better electrolyte resistance. And as the proportion of phosphate ions decreases, the aluminum foil after plasma electrolytic oxidation has better bonding properties.

[0017] Preferably, the plasma electrolytic oxidation solution comprises raw materials in the following concentrations: 0.1-0.2 mol / L zinc acetate, 0.01-0.03 mol / L disodium ethylenediaminetetraacetate and 0.015-0.08 mol / L sodium hexametaphosphate.

[0018] When the components of the plasma electrolytic oxidation solution adopt the above-mentioned ratio, the aluminum foil after plasma electrolytic oxidation has better electrolyte resistance or bonding performance.

[0019] In a second aspect, the present application provides a method for pretreating an anti-corrosion aluminum foil, which adopts the following technical solution:

[0020] A method for pretreating an anticorrosive aluminum foil comprises the following steps:

[0021] Degreasing treatment: using chemical degreasing agent to pre-treat the aluminum foil to obtain pre-treated aluminum foil;

[0022] Anti-corrosion treatment: The pretreated aluminum foil is connected to the anode of the power supply and then immersed in the above-mentioned plasma electrolytic oxidation solution. The pretreated aluminum foil is then subjected to plasma electrolytic oxidation treatment to form a PEO coating on the surface of the pretreated aluminum foil.

[0023] Compared with other surface modification technologies, plasma electrolytic oxidation has the advantages of simple process, environmental protection, low cost and high production efficiency.

[0024] Preferably, in the anti-corrosion treatment, when the pretreated aluminum foil is subjected to plasma electrolytic oxidation treatment, the temperature of the plasma electrolytic oxidation solution is 35-50°C.

[0025] When the solution temperature is too low, the plasma electrolytic oxidation effect is weak, and the film thickness and hardness values ​​are relatively low. When the solution temperature is too high, the plasma electrolytic oxidation liquid enhances the dissolution effect on the oxide film layer, causing the film thickness and hardness to decrease significantly, and the plasma electrolytic oxidation liquid is prone to splashing, and the oxide film layer is also prone to being partially burned or broken down. When the above temperature is used, the oxide film layer grows faster, the film is denser, and the performance is better.

[0026] Preferably, in the anti-corrosion treatment, when the pre-treated aluminum foil is subjected to plasma electrolytic oxidation treatment, the parameters of the pulse power supply are: the current density is 5-15A / dm 2 , the duty cycle is 5-25%, the frequency is 500-1000Hz, and the processing time is 5-20min.

[0027] As the current density increases, the growth rate of the oxide film gradually increases, the thickness and hardness of the oxide film continue to increase, and the roughness of the oxide film surface also gradually increases. However, when the current density exceeds 15A / dm 2 When the oxide film is burned, it is easy to appear burn-out.

[0028] High frequency can promote the growth rate of oxide film, but the thickness is thin and the surface of oxide film is relatively flat. Low frequency can form more large and deep holes, but the sample is also very easy to burn or break through.

[0029] As the oxidation time increases, the thickness of the oxide film gradually increases and the roughness also gradually increases, but there are critical values ​​for the thickness and roughness of the oxide film.

[0030] In summary, when the parameters of the pulse power supply are the above data, the obtained oxide film layer has relatively good thickness, roughness, hardness, growth rate and qualified rate.

[0031] Preferably, in the degreasing treatment, the chemical degreasing agent includes 5-10 g / L sodium hydroxide and 10-15 g / L sodium carbonate, and the solvent of the chemical degreasing agent is ethanol.

[0032] When the chemical degreaser acts on the surface of the aluminum foil, sodium hydroxide first reacts with the grease on the surface of the aluminum foil to generate soluble soaps, and the generated soaps gradually form fine emulsified particles under the action of sodium carbonate, thereby separating the oil from the surface of the aluminum foil and achieving the effect of degreasing and cleaning.

[0033] Preferably, in the degreasing treatment, the chemical degreasing agent further comprises 5-10 g / L hydrotalcite and 10-15 g / L methoxysilane, the degreasing temperature is 70-90° C., and the degreasing time is 2-4 h.

[0034] As a surfactant, methoxysilane can penetrate between the aluminum foil and the grease, thereby infiltrating, emulsifying, and loosening the grease, thereby reducing the adhesion of the grease to the metal. Moreover, after the grease is separated from the surface of the aluminum foil, methoxysilane can also effectively prevent the grease from adhering to the surface of the aluminum foil again through solubilization. Hydrotalcite is also a hydrophobic and lipophilic mineral component, which can also promote the separation of grease particles from the surface of the aluminum foil, further improving the degreasing effect of the chemical degreasing agent.

[0035] In addition, within the temperature range of 70-90°C, the hydroxyl groups on the surface of the hydrotalcite can gradually detach from and attach to the surface of the aluminum foil, while the silanol groups of the methoxysilane can undergo a condensation reaction with the hydroxyl groups on the surface of the aluminum foil, thereby forming a network-structured silane film on the surface of the aluminum foil, further improving the electrolyte resistance and bonding properties of the aluminum foil after plasma electrolytic oxidation.

[0036] In a third aspect, the present application provides an aluminum-plastic film, which adopts the following technical solution:

[0037] An aluminum-plastic film, the laminated structure of which is, from the outside to the inside, an outer material layer, an outer adhesive layer, an outer primer layer, an outer PEO coating layer, an aluminum foil layer, an inner PEO coating layer, an inner primer layer, an inner adhesive layer, and an inner heat-sealing layer; the outer PEO coating layer and the inner PEO coating layer are both obtained by treating the aluminum foil layer with the anti-corrosion aluminum foil pretreatment method.

[0038] When the anti-corrosion aluminum foil layer is treated by the above-mentioned anti-corrosion aluminum foil pretreatment method, it not only has excellent corrosion resistance to the electrolyte inside the battery, but also has better bonding properties with other layers of the aluminum-plastic film.

[0039] In summary, this application has the following beneficial effects:

[0040] 1. The electrolyte used in plasma electrolytic oxidation abandons chromate, thus directly eliminating the possibility of improper disposal of chromate causing harm to the environment and affecting aquatic life;

[0041] 2. Compared with sodium silicate solution, when phosphate solution is used as electrolyte, aluminum foil after plasma electrolytic oxidation has better bonding performance and electrolyte resistance;

[0042] 3. Introducing zinc ions into the plasma electrolytic oxidation solution effectively enhances the crystallinity of the oxide film layer and further improves the electrolyte resistance of the aluminum foil after plasma electrolytic oxidation;

[0043] 4. Zinc ions can form zinc phosphate coating on the surface of aluminum foil with phosphate ions. The zinc phosphate coating can form a complex complex with aluminum ions in the aluminum foil, thereby making the aluminum foil after plasma electrolytic oxidation have better electrolyte resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 It is a structural schematic diagram of the aluminum-plastic film in this application.

[0045] Explanation of the accompanying drawings: 1. Outer material layer; 2. Outer adhesive layer; 3. Outer primer layer; 4. Outer PEO coating layer; 5. Aluminum foil layer; 6. Inner PEO coating layer; 7. Inner primer layer; 8. Inner adhesive layer; 9. Inner heat sealing layer. DETAILED DESCRIPTION

[0046] The present application is further described in detail below with reference to the accompanying drawings and embodiments.

[0047] raw material

[0048] Zinc acetate CAS: 557-34-6; Disodium ethylenediaminetetraacetate CAS: 139-33-3; Sodium hexametaphosphate CAS: 10124-56-8; Sodium phosphate CAS: 7601-54-9; Zinc phosphate CAS: 7779-90-0; Sodium hydroxide CAS: 1310-73-2; Sodium carbonate CAS: 497-19-8; Hydrotalcite CAS: 12304-65-3, 800 mesh; Methoxysilane CAS: 2487-90-3; Ethanol CAS: 64-17-5;

[0049] Trivalent chromium passivator - Henkel ALODINE5992; nylon film - Japan Unitika NLM; PET / nylon film - Japan Gunze HLB; polyurethane adhesive - Toyo Morton LIS-8410-CN; acrylic resin - Tosoh Chemical; inner layer adhesive - Yantai MX-8347; maleic anhydride modified cast polypropylene film (CPP) - Nanya DE.

[0050] It should be noted that the models of the above raw materials are not the only options, and the models of the above raw materials can be selected arbitrarily from commercially available products according to actual needs.

[0051] Example

[0052] Example 1

[0053] A method for pretreating an anticorrosive aluminum foil comprises the following steps:

[0054] Degreasing treatment: The aluminum foil is pretreated with a chemical degreasing agent for degreasing for 3 hours (2-4 hours is acceptable) to obtain a pretreated aluminum foil; wherein the chemical degreasing agent can be a commercially available acidic degreasing agent or alkaline degreasing agent. In this embodiment, the chemical degreasing agent is an ethanol solution of sodium hydroxide and sodium carbonate, with a sodium hydroxide concentration of 8 g / L and a sodium carbonate concentration of 13 g / L;

[0055] Anti-corrosion treatment: The pretreated aluminum foil is connected to the anode of the power supply and then immersed in the plasma electrolytic oxidation solution. The aluminum foil is then subjected to plasma electrolytic oxidation treatment using a pulse power supply, and an external water cooling system is used to maintain the temperature of the electrolyte solution at 45°C during the treatment, so that a PEO coating is formed on the surface of the aluminum foil;

[0056] The plasma electrolytic oxidation liquid is a mixed aqueous solution of zinc acetate, disodium ethylenediaminetetraacetate and sodium hexametaphosphate, the concentration of zinc acetate is 30g / L, the concentration of disodium ethylenediaminetetraacetate is 10g / L, and the concentration of sodium hexametaphosphate is 30g / L; the parameters of the pulse power supply are: the current density is 10A / dm 2 , the duty cycle is 15%, the frequency is 700Hz, and the processing time is 10min.

[0057] Embodiment 2-7

[0058] The difference from Example 1 is that the concentrations of the components in the plasma electrolytic oxidation solution are different, as shown in Table 1. It should be noted that the addition amount of disodium ethylenediaminetetraacetate has little effect on the final experimental data, and it can be arbitrarily selected from 0.01-0.03 mol / L. In Examples 1-7, 0.02 mol / L is used as an example for description.

[0059] Table 1 Concentration of each component in the plasma electrolytic oxidation solution in Examples 1-7 (mol / L)

[0060] Zinc acetate Disodium EDTA Sodium Hexametaphosphate Example 1 0.15 0.02 0.05 Example 2 0.20 0.02 0.015 Example 3 0.10 0.02 0.08 Example 4 0.25 0.02 0.005 Example 5 0.05 0.02 0.10 Example 6 0.15 0.02 0.015 Example 7 0.15 0.02 0.08

[0061] Example 8

[0062] The difference from Example 1 is that the plasma electrolytic oxidation liquid is a zinc phosphate aqueous solution, and the concentration of zinc phosphate is 0.05 mol / L.

[0063] Example 9

[0064] The difference from Example 1 is that the plasma electrolytic oxidation liquid is a sodium phosphate aqueous solution, and the concentration of sodium phosphate is 0.1 mol / L.

[0065] Example 10

[0066] The difference from Example 1 is that the degreasing agent further includes hydrotalcite and methoxysilane, the concentration of hydrotalcite is 8 g / L, the concentration of methoxysilane is 13 g / L, and the degreasing temperature is 80° C. (preferably 70-90° C.).

[0067] Examples 11-15

[0068] The difference from Example 10 is that the concentrations of the components of the degreasing agent are different, as shown in Table 2.

[0069] Table 2 Concentration of each component of the degreasing agent in Examples 10-14 (g / L)

[0070] Sodium hydroxide Sodium carbonate Hydrotalcite Methoxysilane Example 10 8 13 8 13 Embodiment 11 5 10 5 10 Example 12 10 15 10 15 Example 13 3 8 3 8 Embodiment 14 13 17 13 17

[0071] Examples 15-18

[0072] The difference from Example 1 is that during the anti-corrosion treatment, the temperature of the electrolyte solution is different, as shown in Table 3.

[0073] Table 3 Temperature of electrolyte solution in anticorrosion treatment of Example 1 and Examples 15-18 (°C)

[0074] Example 1 Embodiment 15 Example 16 Embodiment 17 Embodiment 18 temperature 40 35 50 25 60

[0075] Examples 19-22

[0076] The difference from Example 1 is that the parameters of the pulse power supply are different during the anti-corrosion treatment, as shown in Table 4.

[0077] Table 4 Pulse power supply parameters in anti-corrosion treatment of Example 1, Example 19-22

[0078] Current density (A / dm2) Duty cycle (%) Frequency (Hz) Processing time (min) Example 1 10 15 700 10 Embodiment 20 5 5 50 5 Embodiment 21 15 25 1000 20 Embodiment 22 3 3 30 3 Embodiment 23 20 30 1200 25

[0079] Comparative Example

[0080] Comparative Example 1

[0081] The difference from Example 1 is that the plasma electrolytic oxidizing liquid is replaced by a trivalent chromium passivating agent - Henkel ALODINE5992, and the use parameters include a concentration of 5%, immersion treatment for 5 minutes at room temperature, and a pH value of 4. For specific operations, please refer to the product technical manual of Henkel ALODINE5992.

[0082] Comparative Example 2

[0083] The difference from Example 1 is that the plasma electrolytic oxidation liquid is replaced by a sodium silicate aqueous solution, and the concentration of the sodium silicate is 0.1 mol / L.

[0084] Comparative Example 3

[0085] The difference from Example 1 is that no antiseptic treatment was performed.

[0086] Application Examples

[0087] Application Examples 1-22

[0088] An aluminum-plastic film, whose laminated structure from the outside to the inside is: an outer material layer 1, an outer adhesive layer 2, an outer primer layer 3, an outer PEO coating layer 4, an aluminum foil layer 5, an inner PEO coating layer 6, an inner primer layer 7, an inner adhesive layer 8, and an inner heat-sealing layer 9, as shown in the following figure: Figure 1 As shown;

[0089] The outer material layer 1 is a biaxially stretched nylon film or a co-extruded composite film of PET / nylon, with a thickness of 25 μm (15-30 μm is acceptable);

[0090] The outer adhesive layer 2 is a commercially available polyurethane adhesive for lithium battery aluminum-plastic film composite, with a thickness of 4 μm (2-6 μm is acceptable);

[0091] The outer primer layer 3 and the inner primer layer 7 are acrylic resins with a concentration of 8 g / L (preferably 5-10 g / L);

[0092] The outer PEO coating 4, the aluminum foil layer 5 and the inner PEO coating 6 are aluminum foils treated by Example 1-22, and the thickness of the aluminum foil is 40 μm (preferably 30-80 μm);

[0093] The inner adhesive layer is a commercially available inner adhesive for lithium battery aluminum-plastic film composite, with a thickness of 4 μm (3-6 μm is acceptable);

[0094] The inner heat-sealing layer 9 is a commercially available cast polypropylene film (CPP) modified with maleic anhydride, and has a thickness of 80 μm (preferably 30-80 μm).

[0095] Application comparison

[0096] Application Comparative Examples 1-3

[0097] The difference from Application Example 1 is that the outer PEO coating, the aluminum foil layer and the inner PEO coating are aluminum foils treated according to Comparative Examples 1-3.

[0098] Performance testing

[0099] Detection Methods

[0100] 1. Aluminum foil roughness test

[0101] Three samples were randomly selected from Examples 1-22 and Comparative Examples 1-3, and then the roughness of the sample surfaces was tested using a roughness tester (Mitutoyo SJ-310), and the average value was taken.

[0102] 2. Aluminum foil salt spray test

[0103] Three samples were randomly selected from Examples 1-22 and Comparative Examples 1-3, and then the samples were tested using an ASTM B 117 salt spray tester to observe the corrosion morphology of the sample surfaces after 720 hours of salt spray treatment;

[0104] It should be noted that, for the convenience of description, the corrosion morphology of the sample surface is divided into four levels, as follows:

[0105] Level 0: No corrosion spots on the surface;

[0106] Level 1: There are trace corrosion spots on the surface (less than 1%);

[0107] Level 2: There are a few corrosion spots on the surface (1-10%);

[0108] Level 3: There are many obvious corrosion spots on the surface, or obvious corrosion pits and corrosion cracks (more than 10%).

[0109] Test data:

[0110] Table 5 Surface roughness and corrosion resistance of Examples 1-22 and Comparative Examples 1-3

[0111]

[0112] 3. Bonding strength test between aluminum-plastic film CPP / AL

[0113] Three samples were taken from application examples 1-22 and application comparison examples 1-3 respectively, and the samples were cut into rectangular specimens with a width of 15 mm and a length of 200 mm. The peel strength of the samples was then tested in accordance with GB / T8808-1988 "Peeling Test Method for Soft Composite Plastic Materials" and the average value was taken.

[0114] 1. Aluminum-plastic film electrolyte resistance

[0115] Three samples were taken from application examples 1-22 and application comparison examples 1-3, respectively, and the samples were cut into rectangular specimens with a width of 15 mm and a length of 200 mm. The specimens were then immersed in electrolyte (electrolyte composition: EC / DEC / DMC=1 / 1 / 1+1M LiPF6+1000ppm water) and placed in an oven at 85°C for 30 days. The peel strength of the specimens was then tested in accordance with GB / T8808-1988 "Peeling Test Method for Soft Composite Plastic Materials", and the average value was taken. Finally, the difference in peel strength before and after immersion was calculated.

[0116] Test data:

[0117] Table 6 Peel strength and electrolyte resistance performance of application examples 1-22 and application comparative examples 1-3

[0118]

[0119]

[0120] With reference to Examples 1-5 and in combination with Table 5, it can be seen that with the increase in the specific gravity of sodium hexametaphosphate and the decrease in the specific gravity of zinc acetate, the roughness of the surface of the aluminum foil sample gradually increases, and the morphology of the aluminum foil sample after salt spray treatment gradually improves. However, when the concentration of zinc acetate is 0.20 mol / L and the concentration of sodium hexametaphosphate reaches 0.015 mol / L, if the specific gravity of sodium hexametaphosphate is further increased and the specific gravity of zinc acetate is reduced, the roughness of the surface of the aluminum foil sample will gradually decrease, while the morphology of the aluminum foil sample after salt spray treatment will still gradually improve.

[0121] With reference to Example 1, Examples 6-7 and Table 5, it can be seen that when the specific gravity of zinc acetate is maintained at 0.15 mol / L, as the specific gravity of sodium hexametaphosphate increases, the roughness of the aluminum foil sample gradually decreases, and the morphology of the aluminum foil sample after salt spray treatment also gradually improves.

[0122] It can be seen from the reference to application examples 1-5 and in combination with Table 6 that, with the increase of the specific gravity of sodium hexametaphosphate and the decrease of the specific gravity of zinc acetate, the initial peeling force of the aluminum-plastic film sample is gradually improved, and the peeling strength difference of the aluminum-plastic film sample is gradually reduced. However, when the concentration of zinc acetate is 0.20mol / L and the concentration of sodium hexametaphosphate reaches 0.015mol / L, if the specific gravity of sodium hexametaphosphate is increased again and the specific gravity of zinc acetate is reduced again, the initial peeling force of the aluminum-plastic film sample will gradually decrease, while the peeling strength difference of the aluminum-plastic film sample still gradually decreases.

[0123] With reference to Application Example 1, Application Examples 6-7 and in combination with Table 6, it can be seen that when the specific gravity of zinc acetate is maintained at 0.15 mol / L, as the specific gravity of sodium hexametaphosphate increases, the initial peeling force of the aluminum-plastic film sample gradually decreases, while the peeling strength difference of the aluminum-plastic film sample gradually decreases.

[0124] This shows that in the plasma electrolytic oxidation solution, with the increase of the specific gravity of sodium hexametaphosphate, the electrolyte resistance and bonding properties of the aluminum foil after plasma electrolytic oxidation will gradually improve. However, when the concentration of sodium hexametaphosphate reaches 0.05 mol / L, if the concentration of sodium hexametaphosphate is further increased, the bonding properties of the aluminum foil after plasma electrolytic oxidation will gradually decrease. Therefore, in actual use, the concentration of each component in the plasma electrolytic oxidation solution can be selected according to needs.

[0125] With reference to Example 1, Examples 6-8 and in combination with Table 5, it can be seen that the aluminum foil after plasma electrolytic oxidation in Example 8 has similar roughness and morphology after salt spray treatment as the aluminum foil after plasma electrolytic oxidation in Example 1.

[0126] However, compared with the aluminum foil after plasma electrolytic oxidation in Example 6, the roughness of the aluminum foil after plasma electrolytic oxidation in Example 8 is relatively poor. Compared with the aluminum foil after plasma electrolytic oxidation in Example 7, Example 8 has better roughness, but the morphology after salt spray treatment is poor.

[0127] With reference to Application Example 1, Application Examples 6-8 and in combination with Table 6, it can be seen that the aluminum-plastic film of Application Example 8 and the aluminum-plastic film of Application Example 1 have similar initial peeling force and peeling strength difference.

[0128] However, compared with the aluminum-plastic film of Application Example 6, the peel strength difference of Application Example 8 is relatively low, but the initial peel difference of Application Example 8 is also relatively low, and compared with Application Example 7, the initial peel strength of Application Example 8 is greater, but at the same time the peel strength difference is also greater.

[0129] The reason is that the specific gravity of zinc ions and phosphate ions in the 0.05 mol / L zinc sulfate aqueous solution is close to the specific gravity of zinc ions and phosphate ions in the plasma electrolytic oxidizing solution in Example 1, so the samples prepared by the two have similar electrolyte resistance and bonding properties. However, the specific gravity of zinc ions and phosphate ions in the zinc sulfate aqueous solution is constant, and adjusting the proportion of phosphate ions can effectively change the electrolyte resistance or bonding properties of the sample.

[0130] With reference to Examples 8-9 and in combination with Table 5, it can be seen that the sample of Example 9 has similar roughness and morphology after salt spray treatment relative to the sample of Example 8. With reference to Application Examples 8-9 and in combination with Table 6, it can be seen that, relative to the aluminum-plastic film of Application Example 8, the aluminum-plastic film of Application Example 9 has similar initial peel strength, but the difference in peel strength is significantly larger. This shows that, under the premise of ensuring the same phosphate ion concentration, although the addition of zinc ions is difficult to improve the bonding performance of the sample, the addition of zinc ions can effectively increase the electrolyte resistance of the sample.

[0131] Referring to Examples 1-9 and Comparative Examples 1-3 and in combination with Table 5, it can be seen that, relative to Comparative Example 3, Examples 1-9 and Comparative Examples 1-2 have better roughness and morphology after salt spray treatment. Parameters Application Examples 1-9 and Application Comparative Examples 1-3 and in combination with Table 6, it can be seen that, relative to Application Comparative Example 3, Application Examples 1-9 and Application Comparative Examples 1-2 have better initial peel force and peel strength difference.

[0132] This shows that the plasma electrolytic oxidation solutions of Examples 1-9, the trivalent chromium passivation solution of Comparative Example 1, and the sodium silicate solution of Comparative Example 2 all have excellent effects on improving the adhesion performance and electrolyte resistance of aluminum foil.

[0133] Compared with Comparative Example 1, Examples 1-4, 6, 8-9 have similar or higher roughness, and Examples 1-3, 5-9 have similar or better morphology after salt spray treatment. Compared with Comparative Example 1, Examples 1-4, 6, 8-9 have similar or higher initial peeling force, and Examples 1-3, 5, 7-8 have similar or lower peeling strength difference.

[0134] This shows that phosphate or a phosphate mixture at a suitable concentration can effectively replace the trivalent chromium passivating agent.

[0135] Compared with Comparative Example 2, Examples 1-2, 4, 6, 8-9 have similar or higher roughness, and Examples 1-3, 5-9 have better morphology after salt spray treatment. Compared with Comparative Example 1, Examples 1-2, 4, 6, 8-9 have similar or higher initial peeling force, and Examples 1-9 have similar or lower peeling strength difference.

[0136] This shows that phosphate or a phosphate mixture at a suitable concentration can effectively replace sodium silicate.

[0137] With reference to Example 1 and Examples 10-14 in combination with Table 5, it can be seen that, relative to Example 1, the morphologies of Examples 10-14 after salt spray treatment are similar or better, especially the morphologies of Examples 10, 12, and 14 after salt spray treatment are particularly outstanding. With reference to Application Example 1 and Application Examples 10-14 in combination with Table 5, it can be seen that, relative to Application Example 1, the peel strength differences of Application Examples 10-14 are relatively lower, among which Application Examples 10, 12, and 14 are particularly outstanding.

[0138] This shows that hydrotalcite and methoxysilane can effectively enhance the electrolyte resistance of the sample, and with the addition of hydrotalcite and methoxysilane, the electrolyte resistance of the sample gradually improves, but the improvement effect gradually slows down.

[0139] With reference to Example 1 and Examples 15-18 and in combination with Table 5, it can be seen that, relative to Example 1, the performance of Examples 15-16 after salt spray treatment is not much different, and the performance of Examples 17-18 after salt spray treatment is significantly deteriorated. With reference to Application Example 1 and Application Examples 15-18 and in combination with Table 5, it can be seen that, relative to Application Example 1, the difference in peel strength of Application Examples 15-16 gradually increases, and the difference in peel strength of Examples 17-18 further increases.

[0140] This shows that when the solution temperature is less than 40°C, the plasma electrolytic oxidation effect is weak, the film thickness and hardness values ​​are relatively low, and the electrolyte resistance of the sample is poor. When the solution temperature is greater than 40°C, the plasma electrolytic oxidation solution enhances the dissolution of the oxide film layer, causing the film thickness and hardness to decrease significantly, and the electrolyte resistance of the sample is poor.

[0141] With reference to Example 1 and Examples 19-22 and in combination with Table 5, it can be seen that, relative to Example 1, the roughness of Examples 19 and 21 decreases successively, and the roughness of Examples 20 and 22 increases successively, and the performance of Examples 19-22 after salt spray treatment is similar.

[0142] With reference to Application Example 1, Application Examples 19-22 and in combination with Table 6, it can be seen that, relative to Application Example 1, the initial peeling forces of Application Example 19 and Application Example 21 gradually decrease, and the initial peeling forces of Application Example 20 and Application Example 22 gradually increase. Relative to Application Example 1, the difference in peeling strength between Application Example 19 and Application Example 21 gradually increases, and the difference in peeling strength between Application Example 20 and Application Example 22 gradually decreases.

[0143] This shows that with the improvement of various parameters of the pulse power supply, the adhesion performance and electrolyte resistance of the sample are gradually improved, but the improvement rate is gradually slowing down.

[0144] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for pretreating anti-corrosion aluminum foil using a plasma electrolytic oxidizing solution, characterized in that: The plasma electrolytic oxidation solution is a phosphate-containing electrolyte solution; the plasma electrolytic oxidation solution comprises raw materials of the following concentrations: 0.1-0.2 mol / L zinc acetate, 0.01-0.03 mol / L disodium ethylenediaminetetraacetate, and 0.015-0.08 mol / L sodium hexametaphosphate; The anti-corrosion aluminum foil pretreatment method using the plasma electrolytic oxidizing solution comprises the following steps: Degreasing treatment: using chemical degreasing agent to pre-treat the aluminum foil to obtain pre-treated aluminum foil; Anti-corrosion treatment: connecting the pretreated aluminum foil to the anode of the power supply, and then immersing it in the plasma electrolytic oxidation solution, and then performing plasma electrolytic oxidation treatment on the pretreated aluminum foil to form a PEO coating on the surface of the pretreated aluminum foil; In the anti-corrosion treatment, when the pre-treated aluminum foil is subjected to plasma electrolytic oxidation treatment, the parameters of the pulse power supply are: the current density is 5-15A / dm 2 , the duty cycle is 5-25%, the frequency is 500-1000Hz, and the processing time is 5-20min; The chemical degreasing agent comprises 5-10 g / L sodium hydroxide, 10-15 g / L sodium carbonate, 5-10 g / L hydrotalcite and 10-15 g / L methoxysilane, and the solvent of the chemical degreasing agent is ethanol; The temperature of the degreasing treatment is 70-90° C., and the degreasing time is 2-4 hours.

2. The method for pretreating anticorrosive aluminum foil using plasma electrolytic oxidizing liquid according to claim 1, characterized in that: In the anti-corrosion treatment, when the pre-treated aluminum foil is subjected to plasma electrolytic oxidation treatment, the temperature of the plasma electrolytic oxidation solution is 35-50°C.

3. An aluminum-plastic film, characterized in that: The laminated structure of the aluminum-plastic film is, from the outside to the inside, an outer material layer, an outer adhesive layer, an outer primer layer, an outer PEO coating layer, an aluminum foil layer, an inner PEO coating layer, an inner primer layer, an inner adhesive layer, and an inner heat-sealing layer; the outer PEO coating layer and the inner PEO coating layer are both obtained by treating the aluminum foil layer with the anti-corrosion aluminum foil pretreatment method using the plasma electrolytic oxidizing solution according to any one of claims 1 to 2.

Citation Information

Patent Citations

  • High corrosion resistance coating, and preparation method, and electrolyte and application thereof

    CN110685000A